Evaluation of salivary tumor necrosis factor α as a diagnostic biomarker in oral submucosal fibrosis and squamous cell carcinoma of the oral cavity and oropharynx: a cross sectional observational study - Abdul Aziz Shaikh, Sabiha; Denny E, Ceena; Kumarchandra, Reshma; Natarajan, Srikant; Sunny, Johan; Shenoy, Nandita; K. P, Nandita (Frontiers in Oral Health, 2024)
Introduction Tumor necrosis factor α (TNF-α) is known to be associated with chronic inflammation, and its expression has been shown to increase in advanced cancers. Chronic inflammation is a characteristic feature of oral submucous fibrosis (OSMF), which is a potentially malignant disorder (PMD). Squamous cell carcinoma (SCC) is associated with considerable mortality and morbidity and an early detection or monitoring would greatly help in achieving an effective cure. TNF-α was thus evaluated for use as a biomarker in the present study according to the stage of OSMF and histological grade of SCC in the oral cavity and oropharynx. Methods This study included 45 patients divided into 3 groups—OSMF group, SCC group and control group—each comprising 15 participants. Saliva samples were collected from each patient, and salivary TNF-α levels were estimated using an ELISA kit. Results Statistical analysis revealed no significant differences in TNF-α levels among the OSMF, SCC and control groups; however, there was an increase in the salivary TNF-α level in patients with stage 3 disease according to the clinical stage of OSMF, for which the p value was 0.027. Discussion An increase in the TNF-α concentration with increasing clinical stage suggested a role for TNF-α in the spread of OSMF involvement in anatomical structures of the oral cavity and oropharynx. No significant difference in salivary TNF-α levels was noted among the OSMF, SCC and control groups. Conclusion The study showed a positive correlation of TNF-α with increasing stages of OSMF but was not a reliable biomarker in the categorization of the same.